Revolutionizing Math Education: Unleashing the Potential of Web-based Learning Media for Enhanced Mathematical Problem Solving Skills - Setiawan, Herdi; Handican, Rhomiy; Rurisman, Rurisman (Insitut Agama Islam Negeri Kerinci, 2023)
This research aims to develop web-based mathematics learning media with a focus on enhancing students' mathematical problem-solving abilities. The background of the study is based on the urgent need to address challenges in mathematics education and leverage technology to improve learning outcomes. The research method used is a development research with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. Research instruments include student response questionnaires, media and material validation instruments, and mathematical problem-solving test questions. The research results show that the developed web-based learning media is valid and effective in improving students' mathematical problem-solving abilities, as the paired samples t-test yields a significance score of 0.002 (p < 0.05). Students' response to this learning media is positive, and there is a significant improvement in mathematical problem-solving test scores. The conclusion of this research is that the use of web-based learning media has the potential to enrich mathematics education and enhance student learning outcomes. The implications of the research highlight the necessity of integrating technology in education to optimize learning and meet the learning needs of students in the digital era.